Pyrano[2,3-d]-pyrimidinedione Analogues Targeting Active Site of the H. Pylori Urease: Insights from Virtual Screening and ADMET Studies : Insilico Studies of Pyrano[2,3-d]-pyrimidinedione Analogues - Amrutkar, Rakesh; Pawar, Anket; Kulkarni, Utkarsha Suhas; Dabhade, Ganesh (Iranian Journal of Pharmaceutical Sciences, 2025)
To develop the views and application profiles of pyrano[2,3-d]pyrimidinedione, attempts have been made to account for drug/ligand or receptor/protein interactions by categorizing the suitable active site against the crystal structure of plant urease from jack bean (Canavalia ensiformis). The interaction was evaluated using the delta G value as the scoring function. The molecule with the most excellent negative delta G value is considered to have higher binding efficiency to the protein. The ligands AH4, AH8, and AH1 were shown to possess favorable negative values, indicating that these molecules have a greater affinity for the receptor's active site. The present research article also represents the Insilco ADMET and moderate biological activity of pyrano[2,3-d]pyrimidinedione. Some of the analogues exhibit hepatotoxicity and mutagenicity, as well as hERG K+ channel blocking activity. AH1 and AH2 inhibit cytochrome CYP1A2, affecting the metabolism of numerous xenobiotics. The present research work is beneficial for chemists working in the field of medicinal chemistry.